Emerging math-related critical thinking theory in civil engineering practice - Osman, Sharifah (2016)
Engaging critical thinking and mathematical thinking as a two-dimensional perspective in civil engineering practice is consistent with engineering criteria of the Engineering Accreditation Council, Board of Engineers Malaysia. Thus, it is timely and crucial to inculcate critical thinking and mathematical thinking into the current engineering education. Unfortunately, information about the interrelation between these two types of thinking in real engineering practice is not well established in literature. Therefore, this thesis presents an empirical research using a modified grounded theory approach which studied critical thinking and mathematical thinking in real-world engineering practice. The study focused on developing a substantive theory pertaining to these two types of thinking. Data were generated from semi-structured interviews with eight practicing civil engineers from two engineering consultancy firms. Multiple levels of data analysis comprising open coding, axial coding and selective coding were used. The emerging theory, Math-Related Critical Thinking consists of six essential processes of justifying decision reasonably in engineering design process, namely complying requirements, forming conjectures/assumptions, drawing reasonable conclusion, defending claims with good reasons, giving alternative ways/solutions and selecting/pursuing the right approach. The theory explains the interrelation and interaction among the pertinent elements through the process of justifying decision reasonably in dominating orientation. The study contributes useful information in the form of a substantive theory for engineering education, which is aligned with the expectations of engineering program outcomes set by the Engineering Accreditation Council.